The last party : Britpop, Blair and the demise of English rock / John Harris. - Harris, John (Fourth Estate, 2003)
Drawing on interviews from all the major bands of the Britpop era - including Oasis, Blur, Elastica and Suede - and from music journalists, record executives and those close to government, John Harris charts the rise and fall of this cultural movement.